Beyond Priesthood : Religious Entrepreneurs and Innovators in the Roman Empire. - Gordon, Richard L. (Religionsgeschichtliche Versuche und Vorarbeiten Series, 2017)
RGVV (History of Religion: Essays and Preliminary Studies) brings together the mutually constitutive aspects of the study of religion(s)--contextualized data, theory, and disciplinary positioning--and engages them from a critical historical perspective. The series publishes monographs and thematically focused edited volumes on specific topics and cases as well as comparative work across historical periods from the ancient world to the modern era.